Effects of multimodal intervention program among elite weightlifters with knee pain - Joseph, L.; Paungmali, A.; Sitilertpisan, P.; Pirunsan, U.; Chamnongkich, S. (Asian Journal of Sports Medicine, 2020)
Background: There are no previously reported studies on the health care intervention programs to manage knee pain among elite weightlifters.